Program Inovasi Desa Mandiri (IDAMAN) melalui Pemberdayaan Perempuan Desa dalam Pemanfaatan Tanaman Obat Keluarga - Iis Sulastri; Nisa Zuhrifatul Jannah; Afina Rizky Ramadhani; Marwah Masruroh; Dona Dwi Saputri; Nuria Salsabila; Naila Shafa Martiza; Jadhug Alfando; Tri Hilda Sari (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
The Independent Village Innovation Program (IDAMAN) is a community empowerment effort based on local potential. The objectives of the activity are to increase community knowledge about Family Medicinal Plants, optimize vacant land, and improve the skills of PKK groups in processing TOGA products into high-value economic products. The implementation method includes counseling, TOGA cultivation assistance, and training in processing turmeric into ready-to-brew herbal powder. Knowledge evaluation uses pre- and post-tests, the success of the program is assessed based on the level of participation and skills of participants. The results of the activity show that the utilization of vacant land has been successfully developed into TOGA gardens. Education increased participant knowledge by 33%. PKK groups successfully acquired skills in processing turmeric into ready-to-brew herbal powder products, which have a longer shelf life and have the potential to be developed as community business products. The IDAMAN program has proven effective in increasing TOGA utilization, strengthening family health independence, and encouraging women's economic empowerment through the development of herbal products. This program is expected to become a model for sustainable community empowerment in supporting independent village development.